The statistical analysis of data from intercropping experiments - Pearce, S.C.; Gilliver, B. (1978)
When two species are interplanted the interpretation of experimental data presents statistical difficulties because the yields of the two crops will not in general be independent. It is therefore desirable to have a method that will both allow significance levels to be determined and give full importance to the treatment means of the two crops. It is shown that a bivariate analysis of variance can be carried out with little difficulty and precise tests can be based upon it. If it would be helpful to combine the two crops in any way, e.g. on the basis of calorific value or price, the task is readily accomplished.